Adult-onset Asthma and Occupational Exposures - Torén, K; Järvholm, B; Brisman, J; Hagberg, S; Hermansson, B A; Lillienberg, L (Scandinavian Journal of Work, Environment ＆ Health, 1999)
Objectives This study examined certain occupational exposures and the risk for adult-onset asthma. Methods A nested case-referent study of adult-onset asthma was performed on a random population sample (N= 15 813), aged 21 to 51 years. Cases for the study included 2 groups: subjects reporting "physician-diagnosed" asthma (N= 251) and a broader "asthma" group (N= 362). The "asthma" group consisted of subjects with "physician-diagnosed" asthma (N= 251) and subjects reporting asthma-like symptoms without having "physician-diagnosed" asthma (N= 111). The referents (N= 2044) were randomly selected from the whole population sample. The case-referent sample was investigated with a comprehensive questionnaire about occupational exposures, asthma, respiratory symptoms, smoking, and atopy. Odds ratios were calculated with stratification for gender, year of diagnosis, and birth year. Results The highest odds ratio for "physician-diagnosed" asthma was associated with exposure to flour dust [odds ratio (OR) 2.8, 95% confidence interval (95% CI) 1.5—5.2] and the occupational handling of resin-based paints (isocyanates) (OR 3.0,95% CI 1.6—5.9). Exposure to welding fumes, textile dust, and work with glues containing acrylates was also associated with an increased odds ratio for "physician-diagnosed" asthma. Including persons with asthma-like symptoms (ie, the asthma group) showed similar results. Conclusion This population-based case-referent study from Sweden indicates that occupational exposure to acrylate-based compounds and welding fumes is associated with increased risk for adult-onset asthma.